Surgical preferences in anterior cruciate ligament reconstruction: A cross-sectional study in a low-middle income country - José Fernando Sánchez-Carbonel; José Calmet-Rojas; Fabriccio J. Visconti-Lopez; Diego Urrunaga-Pastor; David Torres-Manrique (PLoS ONE, 2025)
Introduction Anterior cruciate ligament reconstruction (ACLR) is one of the most common surgical procedures in sports orthopedics; however, there is a lack of literature related to this topic in Peru. This study aimed to describe the current surgical preferences in ACLR among Peruvian orthopedic surgeons. Methods An analytical cross-sectional study based on an online survey sent to 500 Peruvian orthopedic surgeons, supplemented with physical surveys distributed during the “IX OrthoTrauma Update” congress held in October 2022 in Lima, Peru. The survey collected demographic characteristics (e.g., residence area, health care sector), employment characteristics (e.g., experience as orthopedic surgeon, experience in ACLR), and surgical preferences for ACLR (choice of femoral tunnel drilling technique, choice of graft, tourniquet use). A total of 162 surgeons responded (32.4%). Results A total of 134 responses were analyzed. 50% (n = 67; 95% CI: 41.5–58.5) of orthopedic surgeons had more than 10 years of experience, and 53.7% (n = 72; 95% CI: 45.2–62.1) had less than 5 years of experience in ACLR. Anteromedial portal was the most popular choice for femoral tunnel drilling (62.7%; n = 84; 95% CI: 54.1–70.5). Additionally, 85.1% preferred using autograft and 83.6% (n = 114; 95% CI: 77.9–90.2) of surgeons reported a preference to obtain the graft from hamstrings. Conclusions To our knowledge, this is the first report to describe the surgical preferences for ACLR among Peruvian orthopedic surgeons, revealing a predominant preference for autografts and hamstring tendon grafts, as well as a high frequency of the anteromedial (AM) portal technique and variability in tourniquet use.